Increasing Awareness and Readership of Tribun Jateng Newspaper as Production Manager - Lana Nastiti Mumpuni; Djoko Setyabudi, S.Sos, MM (Interaksi Online, 2016)
Tribun Jateng is a subsidiary of Kompas Gramedia Group, which has its headquarters in Semarang. At first, the name of newspaper is still callled Warta Jateng with the slogan "Straightforward and Friendly", then on 29 April 2013 the name changed to Tribun Jateng with the new slogan "New Spirit of Central Java". Tribun Jateng distribution area was larger than Warta Jateng. Three months after the name change, Tribun Jateng finally have an online portal that is jateng.tribunnews.com. newspaper is advancing by promoting news coverage honest and balanced, as well as writing in a language that is easily understood by the public. Given that the vision of Tribun Jateng newspaper is to be the group's largest regional media publishing business, which is scattered and leading in Central Java, then Tribun Jateng newspaper is working to improve public awareness and readership in Central Java. Event Semarang Youth Community 2016 and Tribun Jateng Green Walk “Melangkah Bersama Paramex” is a number of activities aimed at increasing awareness and readership of Tribun Jateng Newspaper. Semarang Youh Community 2016, is an activity that represents communities in Semarang to gather, introduce and share experiences about their hobby with fellow community and with the public and and aims to increase awareness and readership of Semarang people aged 18-25 years. While activity Tribun Jateng Green Walk “Melangkah Bersama Paramex” has a goal to to increase public awareness and readership in Grobogan, given that Tribun Jateng newspaper in the new few months expanding the territory of newspaper distribution expansion in the region of Grobogan. Production Manager in both events is responsible for supplying the needs of event, such as the creation of design publications, stage, sound, stand, various publishing tools (banners, banners, posters, flyers, and backdrop) and consumption